غرفة الصناعات الغذائية - Selim, Shahat (2019)
As part of the seminar held by the International Food Policy Research Institute (IFPRI) in collaboration with the National Nutrition Committee (affiliated by the Academy for Scientific Research and Technology) , “Research to support the 100 Million Healthy Lives Initiative: Lessons learned and actions for improving nutrition in Egypt”.